Birding in Pratapgarh Teak Forests - Saxena, V. S. (Indian Forester, 1974)
During inspections of field work under Resources Survey Scheme in Dry Teak forests of Pratapgarh Range, Chittorgarh Division, Rajasthan on 8th Feb., '73 fifty two spp. of birds' belonging to 42 genera and 25 families were observed from jeep in a day of 10 hours-8 A.M. to 6 P.M. The maximum number of spp. totalling 10 was recorded from the babbler family Muscicapidae. Eight spp. of these birds were migratory (winter migrants) to India. Among the water loving birds Black winged Stilts. Lapwings Cattle Egrets and the Sarns, Cranes were seen. It was an year of drought in the tract, tanks & ponds did not retain water till even February and hence perhaps other waders and ducks were not found. Some spp, of birds might have escaped notice, one such notable absence being that of Treepie (Dendrocitta vagabonda). This listing of birds might prove useful, as no such earlier record is available for these forests.